1998
DOI: 10.1128/cmr.11.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter upsaliensis : Waiting in the Wings

Abstract: SUMMARY Despite strong epidemiological evidence supporting an important role for Campylobacter upsaliensis as a human enteropathogen, it remains relatively unknown in the realm of clinical microbiology. Clinical studies indicate that infection with this organism usually is associated with benign self-limiting diarrhea. However, more serious illnesses, including spontaneous abortion and hemolytic-uremic syndrome, recently have been associated with human infections. Understanding of the virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 91 publications
1
56
0
2
Order By: Relevance
“…In the Campylobacter genus, C. jejuni is known as an important causative agent of gastroenteritis (Bourke et al, 1998;Lee et al, 2015), and C. coli has also been reported as a leading cause of the illness, accounting for over 5% of cases triggered by Campylobacter (Valenza et al, 2010). Recent studies, however, reported that non-jejuni Campylobacter, including oral Campylobacter species such as C. concisus, C. ureolyticus, and C. rectus are detectable in patients with diarrhea (Vandamme et al, 1989;Lastovica and le Roux, 2000;Bullman et al, 2011b), pointing to the possible relation of these Campylobacter species and gastrointestinal disease.…”
Section: Gastroenteritismentioning
confidence: 99%
“…In the Campylobacter genus, C. jejuni is known as an important causative agent of gastroenteritis (Bourke et al, 1998;Lee et al, 2015), and C. coli has also been reported as a leading cause of the illness, accounting for over 5% of cases triggered by Campylobacter (Valenza et al, 2010). Recent studies, however, reported that non-jejuni Campylobacter, including oral Campylobacter species such as C. concisus, C. ureolyticus, and C. rectus are detectable in patients with diarrhea (Vandamme et al, 1989;Lastovica and le Roux, 2000;Bullman et al, 2011b), pointing to the possible relation of these Campylobacter species and gastrointestinal disease.…”
Section: Gastroenteritismentioning
confidence: 99%
“…C. upsaliensis has been isolated infrequently from poultry, ducks, and shellfish, and not from other food sources [4,22,23]. The main reservoir of C.…”
Section: Introductionmentioning
confidence: 99%
“…These spe-cies, namely C hyointestinalis, [13][14][15] C upsaliensis, [16][17][18][19][20][21][22][23][24] and C fetus, 25 are inhibited by the high amount of cefoperazone contained in the selective medium. 7 26-28 Because most laboratories in the UK routinely use selective culture, these less common species are being missed.…”
mentioning
confidence: 99%